Ethnic disparities in out-of-hospital cardiac arrest: A population-based cohort study among adult Danish immigrants - Rodrigue Garcia; Deepthi Rajan; Peder Emil Warming; Jesper Svane; Christoffer Vissing; Peter Weeke; Carlo Alberto Barcella; Reza Jabbari; Gunnar Hilmar Gislason; Christian Torp-Pedersen; Jørgen Holm Petersen; Fredrik Folke; et al. (Elsevier, 2022)
Summary: Background: Ethnicity might impact out-of-hospital cardiac arrest (OHCA) risk, but it has scarcely been studied in Europe. We aimed to assess whether ethnicity influenced the risk of OHCA of cardiac cause in Danish immigrants and its interplay with risk factors for OHCA and socioeconomic status. Methods: This nationwide study included all immigrants between 18 and 80 years present in Denmark at some point between 2001 and 2020. Regions of origin were defined as Africa, Arabic countries, Asia, Eastern Europe, Latin America, and Western countries. OHCAs with presumed cardiac cause were identified from the Danish Cardiac Arrest Registry. Findings: Overall, among 1,011,565 immigrants, a total of 1,801 (0.2%) OHCAs (median age 64 (Q1-Q3 53-72) years, 72% males) occurred. The age- and sex- standardized (reference: Western countries) incidence of OHCA (/1,00,000 person-years) was 34.6 (27.8-43.4) in African, 34.1 (30.4-38.4) in Arabic, 33.5 (29.3-38.2) in Asian, 35.6 (31.9-39.6) in Eastern European, and 16.2 (9.0-27.2) in Latin American immigrants. When selecting Western origin as a reference, and after adjusting on OHCA risk factors, Arabic (HR 1.18, 95%CI 1.04-1.35; P=0.01), Eastern European (HR 1.28, 95%CI 1.13-1.46; P<0.001), and African origin (HR 1.34, 95%CI 1.10-1.63; P<0.01) were associated with higher risk of OHCA, whereas Latin American origin (HR 0.58, 95%CI 0.35-0.0.96; P=0.03) was associated with lower risk of OHCA. Comparable results were observed when adjusting on education level and economic status. Interpretation: This study emphasizes that ethnicity is associated with OHCA risk, even when considering traditional cardiac arrest risk factors. Funding: R Garcia received a grant from the Fédération Française de Cardiologie for his post-doctoral fellowship and this work was supported by the Novo Nordisk Foundation Tandem Programme 2022 (grant# 31364).